Heterogeneous structure design for stable Li/Na metal batteries: Progress and prospects - Hongyang Chen; Junxiong Wu; Manxian Li; Jingyue Zhao; Zulin Li; Manxi Wang; Xuan Li; Chuanping Li; Xiaochuan Chen; Xiaoyan Li; Yiu-Wing Mai; Yuming Chen (eScience)
The growth of dendrites in Li/Na metal batteries is a multifaceted process that is controlled by several factors such as electric field, ion transportation, temperature, and pressure. Rational design of battery components has become a viable approach to address this challenge. Among the various design strategies, heterogeneous structures have been demonstrated to be effective in mitigating uneven metal deposition by reducing the local current density and regulating the deposition sites. In this review, we discuss comprehensively the underlying principles and factors that influence dendrite growth, as well as the synthesis approaches for heterogeneous structures. Furthermore, we provide an overview of the diverse applications of heterogeneous structures in battery components. Finally, we highlight existing challenges and future directions for the use of heterogeneous structures in regulating metal deposition.